Pengaruh Shopping Lifestyle dan Promosi terhadap Impulse Buying pada Pelanggan Shopee - Fitriani Fitriani; Rani Ramdayani (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2026)
The rapid growth of e-commerce in Indonesia has intensified competition among online shopping platforms, encouraging companies to implement strategies that stimulate unplanned consumer purchases. One prominent phenomenon arising from this condition is impulse buying, particularly among university students as active digital consumers. This study aims to examine the influence of shopping lifestyle and promotion on impulse buying behavior among Shopee users who are students of STIE Dharma Agung Indonesia. A quantitative research approach was employed using a survey method. Data were collected through online questionnaires distributed to 76 respondents who met the research criteria. The measurement scale used was a five-point Likert scale. Data analysis was conducted using multiple linear regression analysis supported by validity tests, reliability tests, classical assumption tests, t-tests, F-tests, and coefficient of determination analysis. The results indicate that shopping lifestyle has a positive and significant effect on impulse buying. Promotion also shows a positive and significant influence on impulse buying behavior. Simultaneously, shopping lifestyle and promotion significantly affect impulse buying. The coefficient of determination (R²) value of 0.594 indicates that 59.4% of impulse buying behavior is explained by shopping lifestyle and promotion, while the remaining 40.6% is influenced by other factors not examined in this study. These findings suggest that promotional strategies and consumer shopping lifestyles play an important role in encouraging impulse buying in e-commerce platforms.